Review: Cell cycle aberrations and neurodegeneration - Bonda, D. J. (Neuropathol Appl Neurobiol, 2010)
The cell cycle is a highly regulated and fundamental cellular process that involves complex feedback regulation of many proteins, and any compromise to its integrity elicits dire consequences for the cell. For example, in neurodegenerative diseases such as Alzheimer disease (AD), evidence for abnormal cell cycle re-entry precedes other hallmarks of disease and as such, implicates cell cycle aberrations in the aetiology of AD. The mechanism(s) for cell cycle re-entry in AD, however, remain unclear. Current theory suggests it to be part of a combination of early events that together elicit the degenerative pathology and cognitive phenotype consistent with the disease. We propose a ‘Two-Hit Hypothesis’ that highlights the concerted interaction between cell cycle alterations and oxidative stress that combine to produce neurodegeneration. Here, we review the evidence implicating cell cycle mechanisms in AD and how such changes, especially in combination with oxidative stress, would lead to a cascade of events leading to disease. Based on this concept, we propose new opportunities for disease treatment.